Marketplace Strategic Positioning Analysis - Yasir Maulana; Ayus Ahmad Yusuf; Puspo Dewi Dirgantari; Ratih Hurriyati (UIN Siber Syekh Nurjati Cirebon, 2023)
This study aims to examine the impact of positioning strategy variables consisting of Attributes, Benefits, Users, Competitors, Category, and Price on Consumer Purchase Decisions. The objects in this Research are Uniku management department students. The population is all Uniku management department students buying stuff from the online marketplace. The sample amount in this study is 140 respondents—the instrument of data collection using questionnaires that have fulfilled the validity and reliability requirements. We use multiple linear regression to analyze the impact. Based on the study results, the Attribute, User, Competitor, and Category variables have no effect on Purchase Decisions in the Tokopedia Marketplace. Meanwhile, the Benefit and Price variables partially have a significant positive effect on Purchase Decisions in the Tokopedia Marketplace. The regression coefficients of Attributes, Benefits, User, Categories, and Prices simultaneously affect Purchase Decisions in the Tokopedia Marketplace